Australian Women's Art Register an all volunteer run organisation. - Women's Art Register of Victoria (Richmond [Vic.] : Women's Art Register., 2003)
Website of: Women's Art Register, an archive and repository of slides, published material and other written sources, both old and new, documenting Australian women artists, their images and their writings. The organisation facilitates contact between artists and clients providing a range of consultancy services as arranging artists talks and providing lectures to educational institutions and professional groups. Includes information about the organisation, resources, news and events, featured artist, publication and links to members' sites and other art related websites.
Title from home page (viewed on Feb. 26, 2007)
Text and graphics.
Mode of access: World Wide Web
Selected for archiving
Keywords: Women's Art Register of Victoria; Women artists -- Australia